Calvin is looking at the ages of 4 students on Brilliant. Being extremely bored, he decides to add them up 3 at a time, and obtains the values 44, 51, 53, 56. What is the sum of the ages of all 4 students?
Details and assumptions
As an explicit example, if the ages were 1, 2, 3 and 4, then the values that he would obtain when adding them up 3 at a time will be 1 + 2 + 3 = 6 , 1 + 2 + 4 = 7 , 1 + 3 + 4 = 8 and 2 + 3 + 4 = 9 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good clean approach.
As a note on Latex, you can use the cases environment to get the left bracket, instead of using the array environment along with "\left{ \right."
Ah, thank you very much. I will keep that in mind :)
Let their ages be a,b,c,d. Then we have a+b+c=44 b+c+d=51 c+d+a=53 d+a+b=56 Adding all these we have 3(a+b+c+d)=204 So a+b+c+d=68 So ans is 68
A+B+C=44 , A+B+D=51 , A+C+D=53 , B+C+D=56 than we sum them all 3A+3B+3C+3D=204 , A+B+C+D=68
From our information, we find the following system of equations, where x i is the score of the i th student:
x 1 + x 2 + x 3 = 4 4
x 1 + x 2 + x 4 = 5 1
x 1 + x 3 + x 4 = 5 3
x 2 + x 3 + x 4 = 5 6
(Note that it does not matter which students are which.)
Adding all of these equations together, we find 3 x 1 + 3 x 2 + 3 x 3 + 3 x 4 = 2 0 4 → x 1 + x 2 + x 3 + x 4 = 6 8
great answer
Let w, x, y, and z be the ages of the 4 students. We can create the sum 3w+3x+3y+3z=44+51+53+56 when we add the 4 equations together. Dividing both sides by 3 gives us the sum w+x+y+z, which is 68
Let the ages of 4 students be a,b,c,d. Sum of 3 at a time (a+b+c) + (b+c+d)+(c+d+a)+(d+a+b) is 44+51+53+56=204 now solving the above we get 3 times a+b+c+d equals 204.. sum a+b+c+d equals 68.
Now by the data given above, we kvow that d is bigger than c -- 7
And we also know that c is bigger than b -- 2
We also know that * b* is bigger than a --3
So, by some trial and error , a = 12 b = 15 c = 17 d = 24
Thus , 12+15+17+24 = 68
Let x, y , z be the digits of N , then
N = xyz = 100x + 10y +z = a^{2} and by increasing the digits
100(x+1) + 10(y+2) + z + 3 = b^{2} say .
Now (b+a)(b-a) = b^{2} - a^{2} = 123 = 3\times41 .
taking (b+a) = 41 and (b-a)= 3 we get 2a = 38
or a = 19
so a^{2}= 361 = N
let the 4 ages be a , b , c and d .
a + b + c = 4 4 [ 1 ]
a + b + d = 5 1 [ 2 ]
a + c + d = 5 3 [ 3 ]
b + c + d = 5 6 [ 4 ]
from [ 1 ] + [ 2 ] + [ 3 ] + [ 4 ] , we get the equation 3 a + 3 b + 3 c + 3 d = 2 0 4 . By dividing the whole equation by 3, we get a + b + c + d = 6 8 , which is what we are looking for as a + b + c + d is the sum of the 4 ages
Let the students ages be a,b,c,d. From the details and assumptions,let
a+b+c=44
b+c+d=51
c+d+a=53
a+b+d=56
Summing all four will give 3(a+b+c+d)=204 which implies
Sum of their ages=a+b+c+d=68
Hence,answer is 68.
w + x + y = 4 4
x + y + z = 5 1
y + z + w = 5 3
z + w + x = 5 6
3 w + 3 x + 3 y + 3 z = 2 0 4
w + x + y + z = 6 8
Let the ages of four students be a , b , c , d respectively, then according to question,we have 1. a + b + c = 44 2. b + c + d = 51 3. a + c * * + d = 53 4. a + b + d = 56 Adding equations 1 , 2 , 3 ,& 4 ,we have-
3 * ( a + b + c + d ) = 44 + 51 + 53 + 56 ( *a * + b + c + d ) = 204 / 3 = 68
Let, a b c and d be the ages, given that: a+b+c=44 , a+b+d=51 , a+c+d=53, b+c+d=56 , adding up all these equations gives us: 3a+3b+3c+3d=204 => 3(a+b+c+d)=204 => a+b+c+d=68
The sum of all partial sums is equal to thrice the total age.
Let us assume the ages of the children be - a,b,c,d
we see that the sum of the ages of the first 3 children namely a,b,c=44
So a+b+c=44 so b+c+d=51 so c+d+a=53 so d+a+b=56
on adding the equations- 3(a+b+c+d)=204 so a+b+c+d= 204/3 =68
Let a + b + c = 4 4 , b + c + d = 5 1 , c + d + a = 5 3 , d + a + b = 5 6 so 3 a + 3 b + 3 c + 3 d = 2 0 4 , a + b + c + d = 6 8 _ a n s
Problem Loading...
Note Loading...
Set Loading...
Let a , b , c and d be the ages of each of the 4 students. With that in mind, we get the following system by forming all the triples of students
⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ a + b + c = 4 4 a + b + d = 5 1 a + c + d = 5 3 b + c + d = 5 6
If we add all the equations from the system together, we will get
3 a + 3 b + 3 c + 3 d = 2 0 4 ⇒ 3 ( a + b + c + d ) = 2 0 4 ⇒
⇒ a + b + c + d = 6 8 , which is the sum we are looking for.